Analysis of Factors That Influence the ICT Adoption by SMEs in Colombia (2016)
ABSTRACT: Purpose: The objective of this article is to analyze the factors that influence the adoption of Information and Communication Technologies (ICT) by SMEs in Colombia. Design/methodology: To prove empirically these hypotheses, we administered a questionnaire to a sample of 474 SMEs in Colombia regarding the adoption of ICT and independent variables identified in the literature. Then, we conducted a series of multiple regression models using the data we obtained. Findings: We developed a model that identifies a positive relation between new business opportunities that ICT offer and their adoption level. Likewise, this research identified that a lack of confidence in ICT's security and privacy, a perception of ICT cost-benefit unbalance have a negative impact on the implementation of these technologies. Research limitations/implications: This study has limitations that are inherent to cross-sectional research. These restrict the possibility of conducting dynamic analysis between independent and dependent variables. Likewise, the generalization of results is circumscribed to a geographical context and the type of enterprises surveyed. Practical implications: The results of this research provide valuable contributions to decision-making by SMEs' directors and to public policies that foster the implementation of ICT in SMEs based on an analysis of benefits and barriers found in this study. Originality/value: In view of a lack of empirical work that analyzes the implementation of technology in enterprises in emerging countries, this study provides a valuable contribution to the creation of knowledge when attempting to explain the implementation of ICT using a representative sample of SMEs in Colombia identifying the quantitative form of the impact of the benefits and barriers of these technologies.